FAKTOR-FAKTOR YANG MEMPENGARUHI PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI - Dina Intan Puspitaningrum; Laely Aghe Africa (J-MACC, 2024)
Environmental damage is increasing and spreading in Indonesia. Companies, as one of the parties contributing to environmental damage, must fulfill their responsibility in managing the environment, which can be done through Corporate Social Responsibility (CSR) disclosure. Corporate Social Responsibility (CSR) is an activity carried out by companies to fulfill their social responsibility in relation to the company's operations. This study aims to examine the effect of institutional ownership, audit committee, company size, and public ownership on Corporate Social Responsibility (CSR). The population used in this study consists of manufacturing companies listed on the Indonesia Stock Exchange for the period 2017–2019, with a total of 37 companies. Purposive sampling was used to obtain 241 companies that were sampled for the study. The data used were in the form of annual reports published by these companies and were analyzed using multiple linear regression analysis. The results of this study indicate that company size has an effect on Corporate Social Responsibility (CSR). Meanwhile, institutional ownership, audit committee, and public ownership have no effect on Corporate Social Responsibility (CSR).